PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN MELALUI MEDIASI MOTIVASI KERJA PADA KARYA MAS ART GALLERY - Dewi, Ni Luh Putu Ariesta Angga; Utama, I Wayan Mudiartha (E-Jurnal Manajemen, 2016)
Performance is the result of the work produced in terms of both quality and quantity of their work and can be accounted for in accordance with its role within the organization or company, and along with the ability, skills, and skills in completing the work and within a certain period. The purpose of this study was to determine the effect of career development on employee performance through mediation work motivation. This research was conducted in Karya Mas Art Gallery. The number of samples taken are as many as 33 employees, with saturated or census sampling method. Data collected through interviews and questionnaires. Data analysis technique used is path analysis and Sobel-test. Based on the analysis found that the career development and motivation positive and significant impact on employee performance, but motivational variables can not be said as a mediator variable relationship between career development and employee performance. This suggests that a good career development system will improve employee performance.
Keywords: Career Development, Work Motivation, Employee Performance